2015
DOI: 10.2460/javma.247.12.1408
|View full text |Cite
|
Sign up to set email alerts
|

Cervical intervertebral disk herniation in chondrodystrophoid and nonchondrodystrophoid small-breed dogs: 187 cases (1993–2013)

Abstract: Results suggested that there may be breed-specific differences in the characteristics of cervical IVDH in small-breed dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
4
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 7 publications
5
42
4
10
Order By: Relevance
“…This contrasts either with recent [25] or older [26] findings indicating that C2-C3 was the most commonly affected disk in chondrodystrophic dogs presenting cervical IVDH, although only a small number of FBs were mentioned in the most recent report ( n  = 5). In the thoracolumbar area, T13-L1 was the most frequently affected site, followed by L2-L3 and L1-L2 in FB of our study.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This contrasts either with recent [25] or older [26] findings indicating that C2-C3 was the most commonly affected disk in chondrodystrophic dogs presenting cervical IVDH, although only a small number of FBs were mentioned in the most recent report ( n  = 5). In the thoracolumbar area, T13-L1 was the most frequently affected site, followed by L2-L3 and L1-L2 in FB of our study.…”
Section: Discussioncontrasting
confidence: 84%
“…Nonetheless, a single study comparing thoracolumbar Hansen type I IVDH in FB and Dachshunds showed that FBs were younger at the time of surgery [28], even if the number of FBs was limited in this report ( n  = 47). Similarly, studies addressing cervical IVDH revealed a median age ranging between 6 and 8 years old in chondrodystrophic dogs [25, 26, 31]. One hypothesis for this difference could be the fact that intervertebral disk degeneration occurs faster in FB than in other chondrodystrophic breeds.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, intervertebral disc herniation occurs in dogs between 2 and 16 years of age (Cherrone et al 2004, Hakozaki et al 2015, whereas SRMA is most frequently diagnosed in dogs between 3.2 months and 3 years (Tipold & Jaggy 1994, Lowrie et al 2009, Hansson-Hamlin & Lilliehöök 2013. Our results are in agreement with those studies: dogs with CH and older than 36 months are more likely to have a Cervical Spine diagnosis disease with sensitivity of 87.8% and specificity 91.5%.…”
Section: Discussionmentioning
confidence: 98%
“…Changes in such ratios, with larger and longer cranial vertebral bodies, may influence cervical vertebral column biomechanics. Incidence of canine cervical IVDD is highest in cranial cervical locations (18, 28). The relatively larger and longer vertebral bodies in the cranial cervical vertebral column may lead to increased lever arm stresses on the adjacent disk spaces and may contribute to the higher rate of IVDD in these locations.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 15% of IVDD occurs in the cervical vertebral column in dogs (18). CSM is a disease mainly of large and giant breed dogs causing cervical myelopathy due to progressive spinal cord compression (17).…”
Section: Introductionmentioning
confidence: 99%